Pb and Znconcentration in the water, sediment and Tubifex sp living in the Sail River, Pekanbaru - Desita Yohana R; M. Hasbi M. Hasbi; Budijono Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractSail River is one of polluted rivers in Riau. High Pb and Zn concentrations in the water and sediments may affects organisms living in the rivers, including Tubifex. A study aims to understand the Pb and Zn concent in the water, sediment and Tubifexin that river was conducted in October - November 2017. There were 3 stations, in the upstream (St1), in the residential area (St2) and in the downstream (St3). Samplings were conducted 3 times,once/2 weeks. Results indicate that the concentration of Pb in the water, sediment and Tubifex were 0.276 to 0.776 mg/L, 1.249 to 3.643 mg/kg and 3.643 to 5.613 mg/kg. While the Zn concentration in the water, sediment and Tubifex were 0.597 to 0.785 mg/L, 62.165 to 124.329 mg/kg and 83.982 to 94.995 mg/kg respectively. It was concluded that the water, sediments and Tubifex worms from the Sail River were already contaminated with Pb and Zn.Keywords : Heavy metals, polluted rivers, residential area, contaminated